Revealing the decrease of indoleamine 2,3-dioxygenase as a major constituent for B cells survival post-mesenchymal stem cells co-cultured with peripheral blood mononuclear cell (PBMC) of systemic lupus erythematosus (SLE) patients - Dewi Masyithah Darlan; Delfitri Munir; Agung Putra; Iffan Alif; Nur Dina Amalina; Nelva Karmila Jusuf; Imam Budi Putra (Medicinski glasnik, 2022)
Aim: Mesenchymal stem cells (MSCs) have potent immunosuppressive properties to control systemic lupus erythematosus (SLE) disease by inhibiting indoleamine 2,3-dioxygenase (IDO), and increasing regulatory T cells (Treg) to control innate and adaptive immune cells. However, the interaction and mechanism regarding IDO and B cells in the co-culture of MSC and SLE peripheral blood mononuclear cell (PBMCs) remain unclear. This study aimed to investigate the effects of MSCs in controlling B cells through IDO expression in PBMC of SLE patients. Methods: This study used a post-test control group design. MSCs were obtained from human umbilical cord blood and characterized according to their surface antigen expression and multilineage differentiation capacities. PBMCs isolated from SLE patients were divided into five groups: sham, control, and three treatment groups. The treatment groups were treated by co-culturing MSCs to PBMCs with a ratio of 1:10, 1:25, and 1:40 for 72 h incubation. The B cell levels were analysed by flow cytometry with cytometric bead array (CBA) and the IDO levels were determined by ELISA. Results: The percentages of B cells decreased significantly in groups treated by dose-dependent MSCs, particularly in T1 and T2 groups. These findings were aligned with the significant decrease of the IDO level. Conclusion: MSCs control B cells-mediated by a decrease of IDO in PBMC of SLE patients.
Keywords: autoimmune disease; immunoregulation; inflammatory disorder